Implementation of Brainstorming Method to Improve Social Studies Learning Achievement of Grade VIII Junior High School Students - Rohmatul Hidayati Maulidiyah Lidiyah; Jani Jani (STKIP Taman Siswa Bima, 2023)
This research is motivated by the observation data that the researchers did that social studies learning is still low in achievement because it is not appropriate to choose the method in conveying the material. Learning using the brainstorming method, which was carried out at SMP